Physical activity and mental health in sports university students during the COVID-19 school confinement in Shanghai - Wang, Yufei; Li, Youqiang (Frontiers in Public Health, 2022)
Background: In 2022, Shanghai was seriously affected by the COVID-19 pandemic. The government implemented citywide static management for 2 months, as well as all universities in Shanghai, which changed the normal learning and living style of sports students and led to a decline in physical activity level. As the physical activity has a strong correlation with mental health, this study aimed to investigate the current state of physical activity （PA）and mental health of the students in Shanghai University of Sport. It will try to reveal the correlation between PA and depressive symptoms, anxiety symptoms, fear of COVID-19 and smartphone addiction. Methods: A cross-sectional survey was conducted on a random sample of 400 students who came from six different majors in May 2022 at the Shanghai University of Sport. Respondents completed the International Physical Activity Questionnaire Short Form (IPAQ-SF), the Chinese version of the 9-item Patient Health Questionnaire (PHQ-9), the Chinese version of the Generalized Anxiety Disorder Scale (GAD-7), the Chinese version of the COVID-19 Fear Scale (FCV- 19S), and the Smartphone Addiction Scale (SAS-SV). Demographics, PA, depressive symptoms, anxiety symptoms, fear of COVID-19, and smartphone addiction were compared. A binary logistic regression model was used for the further analysis. Results: A total of 376 college students were included in the final analysis. Binary logistics analysis showed that moderate physical activity （MPA）was negatively correlated with depression (OR=0.95, 95%CI= 0.93-0.98), anxiety (OR=0.97, 95%CI= 0.95-0.99) , fear of COVID 19(OR=0.99, 95%CI= 0.98-0.99)and smartphone addiction (OR= 0.94, 95%CI= 0.9-0.98) (all P < 0.05). Sedentary behavior was positively correlated with smartphone addiction (OR=1.01, P < 0.01, 95%CI= 1.001-1.004). Conclusions: There was an association between the presence of MPA and depressive symptoms, anxiety symptoms, fear of COVID-19, smartphone addiction, and sedentary behavior associated with smartphone addiction levels. Clarifying the causal relationship between PA and mental health will require further research.